Platelets and the Lectin Pathway of Complement Activation in Patients with Systemic Lupus Erythematosus or Antiphospholipid Syndrome - Vils, Signe Risbøl; Troldborg, Anne; Hvas, Anne-Mette; Thiel, Steffen (TH Open, 2023)
Background Patients with systemic lupus erythematosus (SLE) have an increased risk of thrombosis even when they do not have antiphospholipid syndrome (APS). Interactions between complement activation and activated platelets have been suggested in SLE and APS and could play a role in the increased thrombosis risk.Objectives To explore factors potentially related to the prothrombotic pathophysiology in patients with SLE, primary APS, and healthy controls, by investigating lectin pathway proteins (LPPs), complement activation, platelet aggregation, and platelet activation.Methods This cross-sectional cohort study included 20 SLE patients, 17 primary APS, and 39 healthy controls. Flow cytometry and light transmission aggregometry were used to assess platelet activation and aggregation. Using time-resolved immunofluorometric assays, the plasma concentrations of 11 LPPs and C3dg, reflecting complement activation, were measured.Results H-ficolin plasma concentrations were higher in SLE and APS patients than in controls (p = 0.01 and p = 0.03). M-ficolin was lower in SLE than in APS (p = 0.01) and controls (p = 0.03). MAp19 was higher in APS patients than in SLE patients (p = 0.01) and controls (p < 0.001). In APS patients, MASP-2 and C3dg correlated negatively with platelet activation. Platelet-bound fibrinogen after agonist stimulation and C3dg concentrations correlated negatively with platelet activation.Conclusion We observed significant differences between SLE and APS patients regarding complement proteins and platelet activation. Particularly the negative correlations between MASP-2 and C3dg with platelet activation only observed in APS patients suggest that interactions between complement activation and platelets differ in SLE and APS.
Keywords: platelets; complement activation; lectin; systemic lupus erythematosus; antiphospholipid syndrome